Fundamentally different repetitive element composition of sex chromosomes in Rumex acetosa - Jesionek, Wojciech; Bodláková, Markéta; Kubát, Zdeněk; Čegan, Radim; Vyskot, Boris; Vrána, Jan; Šafář, Jan; Puterova, Janka; Hobza, Roman (Annals of botany, 2021)
BACKGROUND AND AIMS: Dioecious species with well-established sex chromosomes are rare in the plant kingdom. Most sex chromosomes increase in size but no comprehensive analysis of the kind of sequences that drive this expansion has been presented. Here we analyse sex chromosome structure in common sorrel (Rumex acetosa), a dioecious plant with XY1Y2 sex determination, and we provide the first chromosome-specific repeatome analysis for a plant species possessing sex chromosomes. METHODS: We flow-sorted and separately sequenced sex chromosomes and autosomes in R. acetosa using the two-dimensional fluorescence in situ hybridization in suspension (FISHIS) method and Illumina sequencing. We identified and quantified individual repeats using RepeatExplorer, Tandem Repeat Finder and the Tandem Repeats Analysis Program. We employed fluorescence in situ hybridization (FISH) to analyse the chromosomal localization of satellites and transposons. KEY RESULTS: We identified a number of novel satellites, which have, in a fashion similar to previously known satellites, significantly expanded on the Y chromosome but not as much on the X or on autosomes. Additionally, the size increase of Y chromosomes is caused by non-long terminal repeat (LTR) and LTR retrotransposons, while only the latter contribute to the enlargement of the X chromosome. However, the X chromosome is populated by different LTR retrotransposon lineages than those on Y chromosomes. CONCLUSIONS: The X and Y chromosomes have significantly diverged in terms of repeat composition. The lack of recombination probably contributed to the expansion of diverse satellites and microsatellites and faster fixation of newly inserted transposable elements (TEs) on the Y chromosomes. In addition, the X and Y chromosomes, despite similar total counts of TEs, differ significantly in the representation of individual TE lineages, which indicates that transposons proliferate preferentially in either the paternal or the maternal lineage.
Keywords: Retroelements; Rumex acetosa; transposable elements; In Situ Hybridization, Fluorescence; Rumex; Sex Chromosomes; sex chromosomes; molekulární evoluce; pohlavní chromozomy; Evolution, Molecular; retroelementy; genome dynamics; satellites; hybridizace in situ fluorescenční; chromozomy rostlin; Chromosomes, Plant